Neural reward processing in paediatric Tourette syndrome and/or attention-deficit/hyperactivity disorder - Akkermans, Sophie E. A.; van Rooij, Daan; Naaijen, Jilly; Forde, Natalie J.; Boecker-Schlier, Regina; Openneer, Thaira J. C.; Dietrich, Andrea; Hoekstra, Pieter J.; Buitelaar, Jan K. (Psychiatry research. Neuroimaging, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is the most common comorbidity in individuals with Tourette syndrome (TS). Yet, it is unclear to what extent TS and ADHD show overlapping or distinct neural abnormalities. ADHD has been associated with altered reward processing, but there are very few studies on reward processing in TS. This study assessed neural activation of basal ganglia and thalamus during reward anticipation and receipt in children with TS and/or ADHD. We analysed mean activations of a priori specified regions of interest during an fMRI monetary incentive delay task. Data was used from 124 children aged 8-12 years (TS n=47, of which 29 had comorbid ADHD; ADHD n=29; healthy controls n=48). ADHD severity across ADHD and TS groups and healthy controls was marginally related to hypoactivation of the right nucleus accumbens during reward anticipation; this effect was not moderated by TS diagnosis. We detected no associations of neural activation with TS. The association between ADHD severity and hypoactivation of the right nucleus accumbens during reward anticipation, independent of the presence or absence of TS, is in line with the view of nucleus accumbens hypoactivation as a dimensional, neurofunctional marker of ADHD severity, transcending the boundaries of primary diagnosis.